Pembentukan Karakter Melalui Katekese Digital: Perspektif Pendidikan Nilai Kristiani - Patrisia Rera Bato; Emmeria Tarihoran (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Seeing that the times are increasingly advanced and everyone cannot be separated from this technology, the author hereby raises the issue of character formation through digital catechesis. This brings new opportunities and challenges in character formation. Digital catechesis, which utilizes digital media to convey catechetical messages, can be an effective tool for reaching the younger generation and helping them develop good character. This study uses qualitative methods by collecting information through literature analysis. Data collection methods involve analyzing and drawing information from various written sources, such as books, scientific journals, and articles. By utilizing technology wisely, digital catechesis can become an integral part of sustainable and meaningful character formation for individuals and their religious communication. Apart from the many benefits of this technological advancement there are also challenges, but by utilizing technology wisely, digital catechesis can become a tool. which is effective in conveying religious messages, forming character, and strengthening spiritual ties in society. Therefore, it is important for the Catholic Church and catechists to take advantage of the opportunities that exist in this digital era to continue the mission of character formation and spreading religious values.